Evaluation of the water purification system consisting of bio-sand filters and titanium dioxide - Rivas, Gema; Flores, Eddysson; Ramírez, Javier (Nexo Revista Científica, 2014)
A batch treatment system (TS) consisting of a biosand filter (BSF) and a filter system packed with titanium dioxide (FSTD) for purifying drinking water was evaluated during 121 days, through the development of the biofilm, TS monitoring, determining the quality of the raw and filtered water, removal efficiencies of BSF and FSTD, and monitoring of arsenic within the effluent TS. The development of the biofilm on the sand surface of the BSF required 31 days and it worked stable in removing turbidity when the raw water varied < 1 up to 31 NTU and decreasing the pH between 7.6-8.3. The quality of the raw water of "La Corona" suggested that only manganese (1.9 mg/L Mn) did not fulfill with the NTON 05 007-98, while only the conductivity (502 μS/cm) and the calcium hardness (53.91 mg/L CaCO3) exceeded CAPRE regulations for the filtered water. The top removal efficiencies of the BSF were 99.9%; 98.46%; 91.76% and 62.16% corresponding to E. coli, turbidity, total iron and ammonium, respectively. Meanwhile, the top removal efficiencies of the FSTD were 30% for manganese and 99.9% for arsenic, removing 40-60 μg/L As of the raw water up to < 10 μg/L As. DOI: http://dx.doi.org/10.5377/nexo.v27i2.1941